Current and emerging avenues for Alzheimer's disease drug targets. (29th August 2019) - Loera‐Valencia, R.; Cedazo‐Minguez, A.; Kenigsberg, P.A.; Page, G.; Duarte, A.I.; Giusti, P.; Zusso, M.; Robert, P.; Frisoni, G. B.; Cattaneo, Annamaria; Zille, M.; Boltze, J.; et al.
Abstract : Abstract: Alzheimer's disease (AD), the most frequent cause of dementia, is escalating as a global epidemic, and so far, there is neither cure nor treatment to alter its progression. The most important feature of the disease is neuronal death and loss of cognitive functions, caused probably from several pathological processes in the brain. The main neuropathological features of AD are widely described as amyloid beta (Aβ) plaques and neurofibrillary tangles of the aggregated protein tau, which contribute to the disease. Nevertheless, AD brains suffer from a variety of alterations in function, such as energy metabolism, inflammation and synaptic activity. The latest decades have seen an explosion of genes and molecules that can be employed as targets aiming to improve brain physiology, which can result in preventive strategies for AD. Moreover, therapeutics using these targets can help AD brains to sustain function during the development of AD pathology. Here, we review broadly recent information for potential targets that can modify AD through diverse pharmacological and nonpharmacological approaches including gene therapy. We propose that AD could be tackled not only using combination therapies including Aβ and tau, but also considering insulin and cholesterol metabolism, vascular function, synaptic plasticity, epigenetics, neurovascular junction and blood–brain barrier targets that have been studied recently. We also make a case for the role of gut microbiota in AD. Our hope is to promote the continuing research of diverse targets affecting AD and promote diverse targeting as a near‐future strategy.